Guritan in Besemah, Pagaralam City: from Sacred to Profane - Luzi, Ahmad Surya; Sunarto, Sunarto; Wadiyo, Wadiyo (Catharsis, 2019)
Guritan is a traditional art of the Besemah community, Pagaralam City which is inherited from one generation to another. Whereas in the guritan there was a change occur which initially as sacred art turns to profane. This thing was what interests the author to discuss the art of guritan. This study aimed at investigating the form of changes in the art of guritan from sacred to profane. The method in this study uses descriptive qualitative with an interdisciplinary approach, while the data collection techniques used observation, interviews, and document studies. The data validity technique uses source triangulation. The data analysis techniques have used the theory from Schoun (2003) with the elaboration of concepts and other supporting data that fits the problem. The results of this study were to provide knowledge and become reference about the initial forms and changes in the art of guritan in Besemah, Pagaralam city. Hopefully, this research can be useful for the public and readers who want to know about the art of guritan in Besemah, Pagaralam City. Because in the text or poetry that is performed in traditional events the marriages contain values, life guidelines, and philosophy that can be applied in the social life of the community with the aim of doing good among fellow humans.